Larry and the cookie - McDaniel, Becky Bring; Martin, Clovis (Chicago : Childrens Press, 1993)
After playing on the slide and swing, riding his bike, and playing basketball and football, Larry has trouble finding the cookie he stashed in his pocket.
"Prepared under the direction of Robert Hillerich, Ph.D.".
1.5.
1.5
K-3
P-2.
Keywords: African Americans -- Fiction; Cookies -- Fiction; Play -- Fiction; Cookies -- Fiction; Play -- Fiction